The Relationship between Employees’ Work Commitment and Organizational Policies (Housing and Urban Development Office of Chaharmahal and Bakhtiari Province) - Meisam Jamalzadeh (Journal of Global Pharma Technology, 2017)
Today, organizations' attention to maximize the capabilities of their employees has substantially grown. However, it should be noted that employees do not necessarily apply all their capabilities to accomplish the objectives of the organization. One of the most important reasons for this is the lack or shortage of organizational commitment of the staff. Accordingly, this study strived to investigate the relationship between employees’ commitment and organizational policies in the Housing and Urban Development Office of Chaharmahal and Bakhtiari province. The research method is applied in terms of the type of research and is a survey method in terms of data collection method. To achieve the research objectives, among from 456 employees of the Housing and Urban Development Office of Chaharmahal and Bakhtiari province, 243 individuals were selected as the study sample. Using a researcher-made questionnaire, employees' commitment and organizational policies were assessed. In order to test the research hypothesis, LISREL software and the structural equation modeling analysis method were used. The results of the study indicated the relationship between different components of organizational policies such as role clarity and role conflict with organizational commitment of the employees.Keywords: Employees’ Organizational Commitment, Organizational Policies, Housing and Urban Development.